A Note on the Yamato Meteorites Collected in December 1969 - Kusunoki, Kou (1975)
P(論文) This paper summarizes earlier studies on 9 "Yamato meteorites" which were discovered in December 1969 by an oversnow traverse party of the 10th Japanese Antarctic Research Expedition at the southeastern end of the Yamato Mountains in East Antarctica. The samples consisted of 8 chondrites and 1 achondrite, among which relatively large 4 samples were classified as follows : Yamato (a) enstatite chondrite, (b) Ca-poor achondrite, (c) carbonaceous chondrite (Type III), and (d) olivine-bronzite chondrite. Since the meteorites were found in the bare ice area of about 5×10km, geomorphological and glaciological features of the sampling site are described in relation to the concentration of the meteorites. departmental bulletin paper